Critical Thinking as a Qualified Decision Making Tool - Turan, Uğur; Fidan, Yahya; Yıldıran, Canan (Journal of History Culture and Art Research, 2019)
Abstract Decision making is a process that we unintentionally apply hundreds of times a day. While the decision-making process for important decisions requires more time-consuming thinking, it can take place instantaneously and spontaneously in situations that have already occurred or where the outcome is not significant. Since decisions are important in human life, it is obvious that the way to make better decisions is to think better and therefore individuals can benefit significantly from having critical thinking skills. In this study, the concepts of decision-making and critical thinking are examined separately to determine the bond and importance between them. The study has a qualitative research feature and a comprehensive literature review and examination have been made. The information obtained as a result of the study conducted within the scope of qualitative research showed that critical thinking is an important requirement for individuals to make better decisions, while various decision-making techniques also contribute positively to the quality of critical thinking of individuals. It is very important for individuals who want to make more successful decisions both in their personal and professional lives, in order to improve their critical thinking capacities and to benefit from decision techniques in making high importance decisions. For today’s and tomorrow’s executives who influence the lives of countless people with their decisions, developing critical thinking skills will be an approach that requires determination and commitment as an indication of their respect for their professions.